2017
DOI: 10.1016/j.talanta.2016.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Use of pyrolyzed paper as disposable substrates for voltammetric determination of trace metals

Abstract: The possibility of using pyrolyzed paper as disposable working electrodes for trace metals determination is reported for the first time. A small piece of pyrolyzed paper (0.7×0.7cm) was positioned at the bottom side of the electrochemical cell using a rubber O-ring, which defined the electrode area (0.48cm; 0.18cm). A large number of electrodes can be obtained from a single piece of standard dimensions (2.5cm×7.5cm) of paper, therefore minimizing the cost per unit. The electrochemical performance of the pyroly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 38 publications
0
25
1
Order By: Relevance
“…It should also be noted that Hg(II) hydrolyzes at high pH to form insoluble hydrated mercury oxides; therefore, this is another advantage for using Bi over Hg in situ electrodes . Moreover, Bi‐film electrodes have been validated many times in the literature for their detection of Zn in aqueous media . In fact, other studies have shown that the Zn stripping peak is only observed in the presence of Bi in the solution .…”
Section: Introductionmentioning
confidence: 99%
“…It should also be noted that Hg(II) hydrolyzes at high pH to form insoluble hydrated mercury oxides; therefore, this is another advantage for using Bi over Hg in situ electrodes . Moreover, Bi‐film electrodes have been validated many times in the literature for their detection of Zn in aqueous media . In fact, other studies have shown that the Zn stripping peak is only observed in the presence of Bi in the solution .…”
Section: Introductionmentioning
confidence: 99%
“…Although, we found that our paper electrodes are better in terms of electrode cost, they are flexible and they do not need to be electrochemical, physical or chemical activated before the analysis as it was shown that happen with screen printed electrodes . Pyrolyzed paper electrodes present several advantages as low cost, easy fabrication, LOD and linear range for Pb detection , which can be a promising option for laboratory applications. However, they present certain limitations for PON application because they are fragile, they could be broken during shipping or the intended use in the adverse conditions usually found when performing analytical work outside a regular laboratory.…”
Section: Resultsmentioning
confidence: 99%
“…The guidelines of the World Health Organization set a safe threshold of Pb in drinking water below 10 ppb . For Point of Need applications disposable electrodes modified with Bi film for heavy metal detection were recently studied .…”
Section: Introductionmentioning
confidence: 99%
“…In the tests performed in the conventional electrochemical system (steady‐state solution), sample or standard solutions were added directly to an electrochemical cell (≈ 25 mL). In this cell, the working electrode area is also defined using a rubber O‐ring, similar to the procedure when pyrolysed paper was used as working electrode .…”
Section: Methodsmentioning
confidence: 99%